Use of combined UASB + eMBR treatment for removal of emerging micropollutants and reduction of fouling - Karen Mora-Cabrera (IWA Publishing, 2021)
This study employs a novel combined pilot plant consisting of an anaerobic reactor followed by a membrane electrochemical bioreactor (eMBR) to treat domestic water containing selected contaminants of emerging concern (CECs) [ibuprofen (IB), carbamazepine (CBZ), diclofenac (DCF) and 17α-ethinylestradiol (EE2)]. The first phase operated as a conventional membrane bioreactor to achieve the removal of organic matter [chemical oxygen demand (COD)], the CECs and phosphorus. A removal rate of 96.3% for COD, 94.5% for IB, 37.1% for CBZ, 87.1% for DCF and 96% for EE2 was obtained. In the three subsequent phases, current density (CD) of 5, 10 and 15 A/m2 was applied successively in the eMBR with the aim of investigating the effects on the removal of the former components and the fouling of the membrane. After the application of 5 and 10 A/m2 CD, the removal rate of COD decreased. Regarding phosphorus, a CD of 5 A/m2 was enough to achieve the rate of 97% and the membrane fouling suffered a substantial reduction too. Finally, the experimental results were subject to statistical analysis using the Kruskal–Wallis and Wilcoxon tests to validate the influence of each CD. HIGHLIGHTS Novel combination of UASB + eMBR technologies proves effective in wastewater treatment.; UASB stands in COD removal, MBR in CECs removal and eMBR in TP removal.; A current density of 5 A/m2 is the most efficient in reducing membrane fouling.; A current density of 5 A/m2 improves the removal of some CECs.;